Analisis Struktur Berpikir Mahasiswa dalam Pembelajaran Matematika - Wahyuningsih, Baiq Yuni (Yayasan Pendidikan Intan Cendekia, 2020)
This study aims to analyze the structure of students' thinking in learning and in problem solving. This type of research is descriptive research with a quantitative approach. Data collection was carried out through questionnaires and test questions. The results of the study showed: a) students with a dominant thinking structure using the left brain seemed less good at socializing well in class both in participating in small group discussions or class discussions. The abilities possessed by these students are usually logical, analytical, reality, factual and procedural; b) students with a dominant thinking structure using the right brain seem to have a personality that likes to interact and socialize but often experience difficulties in learning technical matters so they need to pay more attention when practicing working on questions and c) students with a thinking structure use the right brain and on the left equally classified as students who are active in the learning process. This liveliness is raised in group discussion activities, class discussions and or asking questions personally and expressing ideas/ideas based on logic. Keywords: Structure of Thinking, Learning, Mathematics